Gestational diabetes, preeclampsia and the maternal heart. (3rd October 2022) - Thiru, S; Ansari, F; Cubbon, R; Forbes, K; Chowdhary, A; Jex, N; Kotha, S; Morley, L; Xue, H; Kellman, P; Greenwood, J P; Plein, S; et al.
Abstract: Background: Gestational diabetes mellitus (GDM) and preeclampsia (pE) are both associated with an increased risk of cardiovascular mortality and morbidity, including an increased risk of developing heart failure in later life. Both conditions are increasing in prevalence; GDM affects up to 12% and pE affects 3–5% of pregnancies worldwide. Compromised cardiac energy production is an important contributor to most forms of heart disease. The changes in myocardial energetics in GDM and pE have not been characterised previously. Purpose: We sought to assess if women with GDM and women with pE in the third trimester of pregnancy exhibit adverse cardiac alterations in myocardial energetics, function or tissue characteristics. Methods: Thirty-eight healthy pregnant (HP) women, thirty women with GDM and fifteen women with pE were recruited, matched for age and ethnicity. Participants underwent phosphorus magnetic resonance spectroscopy and cardiovascular magnetic resonance for assessment of myocardial energetics (phosphocreatine to ATP ratio (PCr/ATP)), tissue characteristics, biventricular volumes and ejection fractions, left ventricular (LV) mass, global longitudinal strain (GLS) and mitral in-flow E/A ratio. Results: The biochemical characteristics and multiparametric MR results are given in Table 1. The women in the GDM and the pE groups had higher body-mass index. There was a stepwise increase in the systolic and diastolic BP from the HP to the GDM to the pE group. There was no difference in NTproBNP concentrations between the groups. The gestational weight gain was higher in women with GDM and pE compared to the HP group. The women in the GDM and the pE groups showed similar reductions in myocardial PCr/ATP ratios compared to HP group (Figure 1a), accompanied by lower LV end-diastolic volumes and higher LV mass (Figure 1b) and enhanced LV concentricity in both groups (Figure 1c). While LV ejection fractions were similar across the groups, the GLS was reduced in women with GDM and in women with pE (Figure 1d). Conclusions: We show here for the first time that despite no prior diagnosis of diabetes or hypertension, women with GDM or pE manifest impaired myocardial contractility and higher LV mass, associated with reductions in myocardial energetics. These findings may aid our understanding of the long-term cardiovascular risks associated with these conditions. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Wellcome Trust